2022
DOI: 10.1177/10732748221091394
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a New Integrative Score Based on Various Systemic Inflammatory and Nutritional Indicators in Predicting Prognosis in Patients With Resectable Esophageal Squamous Cell Carcinoma: A Retrospective Cohort Study

Abstract: Background Recent studies revealed that various inflammatory and nutritional indexes were associated with prognosis in esophageal cancer (EC). However, these studies only evaluated one or two indexes, and the prognostic value of these indexes individually or in combination is unclear. This study aimed to construct an integrative score based on various inflammatory and nutritional indexes for prognosis in resectable esophageal squamous cell carcinoma (ESCC). Methods A total of 421 consecutive patients were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Although age (Figure 7K) is controversial for the prognosis of patients with ESCC, it is a good predictor in this experiment. Studies have shown that the nutritional status of patients is also closely related to the prognosis of tumors (10), and MCH, Na, FIB, DBIL, CL (Figures 7H, I, L-N) and other factors also show high predictive ability in this experiment. In addition, the prognosis of patients with ESCC varies with different treatments, and treatment (Figure 7D) (24) is also included in this model.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although age (Figure 7K) is controversial for the prognosis of patients with ESCC, it is a good predictor in this experiment. Studies have shown that the nutritional status of patients is also closely related to the prognosis of tumors (10), and MCH, Na, FIB, DBIL, CL (Figures 7H, I, L-N) and other factors also show high predictive ability in this experiment. In addition, the prognosis of patients with ESCC varies with different treatments, and treatment (Figure 7D) (24) is also included in this model.…”
Section: Discussionsupporting
confidence: 52%
“…Compared with some previous studies, the prognostic ability of our model (three-year AUC 0.761, five-year AUC 0.771) also showed some advantages. In Feng’s experiment ( 10 ), they used laboratory data such as HB and CAR to construct a COHCP model to evaluate the prognosis of ESCC, and its AUC (0.771 for continuous and 0.744 for categorical) showed good predictive ability. In another study, Jayaprakasam’s team ( 22 ) constructed a prognostic model of ESCC using PET and CT, with an AUC of 0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation